Analisis Pengaruh Kinerja Pemasaran Perusahan Logistik Di Semarang - Lisda Rahmasari (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This study aims to: (1) To determine the effect of market orientation on marketing performance; (2) To determine the effect on the performance of the product completeness of marketing; (3) To determine the influence of the effectiveness of distribution channels for marketing performance; (4) To determine the influence of brand equity on marketing performance; (5) To determine the effect of market orientation, the completeness of the product, the effectiveness of distribution channels and brand equity on marketing performance. The sample in this study was 100 consumers Logistic Company in Semarang. Data collection techniques by distributing questionnaires. Type of data is the primary data. Data were analyzed using multiple regression analysis, validity, reliability and classical assumption. Based on the analysis and discussion in the previous section, it can be concluded as follows: Results of regression analysis regression equation: Y = 0.051 + 0.201 + 0.242 X1 X2 + 0.218 + 0.233 X3 X4 + e. Variable dominant or most influential is the completeness of the product with the highest value of regression coefficient, amounting to 24.2%. This indicates that Logistic Company in Semarang has many variations that attract consumers to buy. Based on the results of the t test result that there is a positive and significant effect of market orientation, the completeness of the product, the effectiveness of distribution channels, brand equity on marketing performance. Based on test results obtained figures for 0000 F <0.05 so it can be concluded there is a positive and significant effect of market orientation, the completeness of the product, the effectiveness of distribution channels and brand equity on marketing performance simultaneosly.